Cohesion, team mental models, and collective efficacy: towards an integrated framework of team dynamics in sport - Edson Filho; Gershon Tenenbaum; Yanyun Yang (2014)
A nomological network on team dynamics in sports consisting of a multiframework perspective is introduced and tested. The aim was to explore the interrelationship among cohesion, team mental models (TMMs), collective efficacy (CE) and perceived performance potential (PPP). Three hundred and forty college-aged soccer players representing 17 different teams (8 female and 9 male) participated in the study. They responded to surveys on team cohesion, TMMs, CE and PPP. Results are congruent with the theoretical conceptualisation of a parsimonious view of team dynamics in sports. Specifically, cohesion was found to be an exogenous variable predicting both TMMs and CE beliefs. TMMs and CE were correlated and predicted PPP, which in turn accounted for 59% of the variance of objective performance scores as measured by teams' season record. From a theoretical standpoint, findings resulted in a parsimonious view of team dynamics, which may represent an initial step towards clarifying the epistemological roots and nomological network of various team-level properties. From an applied standpoint, results suggest that team expertise starts with the establishment of team cohesion. Following the establishment of cohesiveness, teammates are able to advance team-related schemas and a collective sense of confidence. Limitations and key directions for future research are outlined.